Investigation of ultra-high performance concrete under static and blast loads - Li, J.; Wu, C.; Hao, Hong; Su, Y. (Multi-Science Publishing Co. Ltd., 2015)
Conventional concrete works as an important construction material. However, conventional concrete is known to be brittle and prone to tensile failure and cracks. To overcome such defects and improve the dynamic performance of concrete against extreme loading conditions, concrete with different additions and formulae have been developed. In a recent study, to develop ultra-high performance concrete (UHPC) material with better strength and crack control ability, super fine aggregates with high pozzolanic effect were mixed into the steel fibre reinforced concrete instead of the traditional graded coarse aggregates. Furthermore, to achieve high early age strength, nanoscale additives which can accelerate the hydration process of the ordinary Portland cement were also introduced into the concrete composite. A series of uniaxial compression and four-point bending tests had been performed in the laboratory to get the material properties of this innovative concrete material. Great improvement of the concrete uniaxial compressive strength and flexural tensile strength was observed. Field blast tests were carried out on columns made of this UHPC material. Superior blast resistance performance was observed. In the current study, based on the available test data, numerical models are developed and numerical simulations are carried out. The simulation results are found to comply well with the experimental results.